2014
DOI: 10.1080/02640414.2014.953979
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-dependent reductions in resting blood pressure following short-term isometric exercise training

Abstract: Word count 2,781 ABSTRACTRecently, a minimum threshold of training intensity for reducing resting blood pressure (RBP) after short-term isometric exercise training (IET; < 4wks) had been suggested.However, variations in IET protocols employed are evident, including different methods for setting training intensity. Therefore, the minimum IET intensity required for RBP adaptations to occur, after short-term IET programs, is not known. Purpose: The purpose of this study was to compare the effects of short-term m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
5
19
0
Order By: Relevance
“…The significant reduction in SBP in our IHG group mirrors the findings of Gill et al who observed a 6.9-mmHg reduction in SBP in normotensive females after 3-weeks of isometric exercise training (IET) (Gill et al 2015). However, Gill et al employed bilateral leg extensions as their mode of IET, thus recruiting a much larger muscle.…”
Section: Discussionsupporting
confidence: 89%
“…The significant reduction in SBP in our IHG group mirrors the findings of Gill et al who observed a 6.9-mmHg reduction in SBP in normotensive females after 3-weeks of isometric exercise training (IET) (Gill et al 2015). However, Gill et al employed bilateral leg extensions as their mode of IET, thus recruiting a much larger muscle.…”
Section: Discussionsupporting
confidence: 89%
“…The current findings (in agreement with Devereux et al 2010) elucidate an intensity dependent continuum of resting blood pressure adaptation whereby Baross et al (2012) reported no significant differences in any RBP parameters at 4 weeks when bilateral-leg extension was performed at an intensity of 85% HRpeak, but significant reductions in SBP and MAP at the end of 8 weeks; whereas Gill et al (2015) showed that all parameters of resting BP were significantly reduced after only 3 weeks of bilateral-leg IET, but only when IET occurred at a higher intensity (~100% HRpeak or 34%MVC) than previously used.…”
Section: Table 2 Here Discussionsupporting
confidence: 85%
“…The resting BP reductions are similar in magnitude to those previously reported following IET that was partly laboratory-based with participants performing constant force contractions (McGowan et al 2007a;Millar et al 2013a) and completely laboratory-based using constant EMG contractions (Devereux et al 2010;Wiles et al 2010;Gill et al 2015). Furthermore, the rate of reduction in all resting BP parameters occurred at either a faster or equal rate (Devereux et al 2010) to that reported previously in normotensive participants following bilateral-leg IET using the same acute programme variables and exercise intensity in a laboratory setting.…”
Section: Table 2 Here Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Evidence for the blood pressure (BP) lowering effects of isometric exercise is growing (Börjesson et al 2016). To date, studies have reported that isometric exercise lowers BP in healthy adults (Wiley et al 1992;Ray and Carrasco 2000;Howden et al 2002;Millar et al 2008;Wiles et al 2010;Devereux et al 2011;Badrov et al 2013a; Devereux and Wiles 2015;Gill et al 2015), hypertensive (non-medicated and medicated) and pre-hypertensive adults (Wiley et al 1992;Taylor et al 2003;McGowan et al 2006;Peters et al 2006;McGowan et al 2007b; Baross et al 2012;Baross et al 2013;Millar et al 2013;Badrov et al 2013b).…”
Section: Introductionmentioning
confidence: 99%